2016
DOI: 10.1007/s10157-016-1267-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of mycophenolic acid in children with clinically stable idiopathic nephrotic syndrome receiving cyclosporine

Abstract: In children with clinically stable INS receiving CyA, C2 monitoring was the most useful single parameter for estimating MPA pharmacokinetics. Younger children required higher MMF doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The search of the literature returned 29 studies meeting the requirements concerning MLR LSSs for MPA and fMPA, dated 1998–2020. We applied 48 MPA LSSs [ 8 , 9 , 14 , 21 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] and five fMPA LSSs [ 35 , 36 , 42 ] found in the literature to calculate the predicted area under the (0–12 h) time–concentration curve (AUC pred ) in children with nephrotic syndrome treated with MMF, and compared the results with AUC total . In the majority of studies, calcineurin inhibitors (CsA or tacrolimus (Tac)) were co-administered with MMF.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The search of the literature returned 29 studies meeting the requirements concerning MLR LSSs for MPA and fMPA, dated 1998–2020. We applied 48 MPA LSSs [ 8 , 9 , 14 , 21 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] and five fMPA LSSs [ 35 , 36 , 42 ] found in the literature to calculate the predicted area under the (0–12 h) time–concentration curve (AUC pred ) in children with nephrotic syndrome treated with MMF, and compared the results with AUC total . In the majority of studies, calcineurin inhibitors (CsA or tacrolimus (Tac)) were co-administered with MMF.…”
Section: Resultsmentioning
confidence: 99%
“…Two of nine the best LSSs included liver transplant recipients [ 28 , 29 ]. Surprisingly, the LSSs established for children with nephrotic syndrome [ 14 , 25 ] or lupus erythematosus [ 21 ] performed poorly as they did not fulfill the criteria: the values of r 2 were below 0.800, and ≤50% of the AUC pred values were within ±15% of the AUC total . These poor results may be explained by one time point equation in the Hibino et al study [ 14 ] and the relatively high intercept.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in patients with frequent relapses show that targeting higher levels of 12-hour area under the curve of mycophenolic acid, ranging from 30 to 45 mg$h/ml, were associated with sustained remission and lower corticosteroid requirement. [46][47][48][49] Similarly, an area under the curve >60 mg$h/ml and a trough concentration >3 mg/ml were associated with remission of proteinuria in children with nephrotic syndrome or lupus nephritis. 50 However, the dose of MMF in the current study was comparable to those reported previously (i.e., 25-35 mg/kg or 800-1200 mg/m 2 20,26,29 including studies that demonstrate pharmacokinetic adequacy.…”
Section: Discussionmentioning
confidence: 97%